NZ-RugbyHealth study: current postural control ability of former rugby union and non-contact sport players - Hume, P. A.: Lewis, G. N.; Brown, S. R. (Sports Medicine, 2023)
Background: Players in contact sports frequently experience mild traumatic brain (concussion) injuries (TBI). While there are known disruptions to balance following acute head trauma, it is uncertain if sport-related concussion injuries have a lasting impact on postural control. Aim: To assess postural control in retired rugby players in comparison to retired non-contact sport players, and to evaluate any association with self-reported sport-related concussion history. Methods: Using a cross-sectional design, 75 players in the NZ-RugbyHealth study from three sports groups (44 ± 8 years; 24 elite rugby, 30 community rugby, 21 non-contact sport) took part in this study. The SMART EquiTest® Balance Master was used to assess participant`s ability to make effective use of visual, vestibular and proprioceptive information using standardised tests. Postural sway was also quantified using centre of pressure (COP) path length. The relationship among sports group, sport-related concussion history and postural control was evaluated using mixed regression models while controlling for age and body mass index. Results: Limited significant differences in balance metrics were found between the sports groups. A statistically significant (p < 0.001) interaction indicated a relationship between COP path length and sport-related concussion history in the most challenging balance condition, such that path length increased as the number of previous sport-related concussions increased. Conclusion: There was some evidence for a relationship between sport-related concussion recurrence in sports players and postural stability in challenging balance conditions. There was no evidence of impaired balance ability in retired rugby players compared with non-contact sport athletes.